Isolated Langerhans Cell Histiocytosis of the Lacrimal Gland in Conjunction With Mucosa-Associated Lymphoid Tissue Lymphoma and Elevated IgG4 Plasma Cells. Issue 4 (July 2019) - Peck, Travis; Bagg, Adam; Zhang, Xiaoming; Armstrong, Blair; Eagle, Ralph C.; Milman, Tatyana
Abstract : Langerhans cell histiocytosis (LCH) is a clonal neoplastic proliferation of Langerhans-type cells. Orbital LCH is infrequent, typically manifesting as an isolated lytic bony lesion with an adjacent soft tissue mass in a child. Isolated lacrimal gland involvement by LCH is extremely rare, with only 2 previously reported cases. The authors describe a 37-year-old woman with a 6-month history of painless right upper eyelid swelling and diffuse right lacrimal gland enlargement without bony changes on computed tomography scan. Excisional biopsy of the lacrimal gland demonstrated concurrent LCH, extranodal marginal zone B-cell lymphoma of mucosa-associated lymphoid tissue, and increased IgG4-expressing plasma cells. Work-up was negative for systemic hematolymphoid malignancy and IgG4-related disease. This case illustrates the association between LCH, mucosa-associated lymphoid tissue lymphoma, and elevated IgG4 plasma cells in the lacrimal gland, and we review the emerging theories proposed to explain this phenomenon. Abstract : This report describes a 37-year-old woman with concurrent Langerhans cell histiocytosis, mucosa-associated lymphoid tissue lymphoma, and elevated IgG4 plasma cells localized to the lacrimal gland.